THE DEVELOPMENT OF MATHEMATICS PROBLEM SOLVING AND ANALYTICAL THINKING ABILITIES FOR GRADE 8 STUDENTS USING 4E×2 INSTRUCTIONAL MODEL - Theeramethakul, Sirinrat; Art-in, Sitthipon (Journal of Graduate MCU KhonKaen Campus, 2020)
The objectives of this study were to : 1) develop the ability to solve mathematical problems. By using the 4E×2 teaching model, students have an average score of not less than 70 percent and the number of students who pass the threshold of 70 percent or more. 2) Develop analytical thinking ability. By using the 4E×2 teaching model, the students have an average score not less than 70% and the number of students who pass the criteria of 70 percent or more. Target groups are students in grade 2 of Ban Nong Bua Thung School. Under the Office of Nakhon Ratchasima Primary Educational Service Area 6, consisting of 12 people. The research model is a 3-part action research tool. The research tools consist of 1) The tools used in the experiment are the learning management plan with pictures. 4E×2 learning styles, consisting of 9 plans, 18 hours duration. 2) The tools used to reflect the performance were teachers’ teaching record, Learning behavior observation form, Student interview form, ended cycle mathematical problem solving ability assessment form which consists of 9 items, and ended cycle analytical thinking ability assessment form which consists of 36 items 3) The tools used in evaluating the effectiveness of learning activities were subjective test of mathematical problem solving ability which contains 10 items, and objective test of analytical thinking ability which contains 30 items. Analyze data by using average, standard deviation and percentage. The results of the research showed that 1) Students have an average mathematical problem solving ability score of 58.33, 72.92 percent of the full score and the number of qualified students is 9 persons; 75.00 percent of all students. Which is higher than the set standard. 2) Students have an average analytical ability score of 22.33 which is 74.44 percent of the full score and the number of qualified students is 9 persons which is 75.00 percent of the total students. Which is higher than the set standard.